Studia na kierunku pedagogika specjalna jako przestrzeń czytania naukowego - Sadowska, Sławomira (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The author describes the properties of modern ways of “reading in science”. It emphasizes the relationship between the type of text (digital, printed) and the kind of reading activity. He points out that reading science texts by scholars is rarely done in full and in linear order. Reading in science, requires active engagement in text, information processing and efficient selection to fully understand content. Analyzing the changes that have taken place with the advent of the C generation, he analyzes “reading in college”. He argues that contemporary students (special education) – representatives of the computerized generation – connected -always clicking – have dropped printed text and are not interested in books as a source of knowledge. Although they have a proficiency in searching online resources, they experience difficulties in using the text and its content. By copying the thesis, the author presents the results of the research conducted in this field and refers to many publications on this subject. Clearly recognizes the need to prepare future students for a rational and critical use of scholarly reading, to learn how to study a scholarly work (both at the earlier stages of education and within the university education system). Also, believes that pedagogical thinking and action derive both from the association with the scientific texts and from reading literature. Reading is an irreplaceable way to enrich the sensitivity and imagination of future teachers (special).